Neuroprotective activity of Indonesian traditional herbal medicine: A systematic review - Mangestuti Agil, Idha Kusumawati, Faisal Akhmal Muslikh, Burhan Ma’arif (Journal of Applied Pharmaceutical Science, 2023)
The brain requires good care for it regulates all systems and functions of the human body’s organs. Good care can also prevent brain damage caused by the ageing process and neurodegenerative diseases. Consuming herbs is one of the treatments for the brain. This study aims to provide an overview of the neuroprotective use of herbs in traditional Indonesian medicine. The method employed is a review of articles based on predetermined criteria. The plants were then reselected based on the plants used for the central nervous system (CNS) in the Cabe Puyang Manuscript. Cabe Puyang is a manuscript that describes the health benefits of various medicinal herbs. According to the criteria, 31 herbs acting as neuroprotective agents in Indonesia were discovered. The herbs were reselected based on the herbs used in the Cabe Puyang Manuscript for the CNS. Twelve herbs have been included in Indonesia’s traditional medicine system for use as neuroprotectors. These herbs are Zingiber officinale, Centella asiatica, Allium sativum, Andrographis paniculata, Piper nigrum, Coriandrum sativum, Piper retrofractum, Moringa oleifera, Ocimum sanctum, Kaempferia galangal, Ruta graveolens, and Acorus calamus. The Cabe Puyang Manuscript mentioned all of the selected herbs used as neuroprotectors in the Indonesian system of medicine. They all demonstrated a strong antioxidative and anti-inflammatory action in brain tissues. Both actions are manifestations of neurodegenerative pathologies.
Keywords: Alternative medicine, neuroprotector, Cabe Puyang, ancient manuscript, herbs